أثر العُرف في أحكام الصّداق: دراسة مقارنة بين الفقه المالكي والتشريع الجزائري - منصور, محمد; مناني, نور الدين (جامعة الوادي - University of Eloued, 2022)
ملخص: لقد اهتمّ كلّ من الشارع الحكيم والمشرع الجزائري بعقد الزواج أيما اهتمام ونظمه تنظيمًا محكمًا، نظرًا لخطورته، فأحاطه بالكثير من الضّوابط والشّروط، التي جاءت في بعض أحكامها موافقة لأعراف النّاس المعتبرة شرعًا، للتيسير ورفع الحرج عليهم. وعليه، لما كان العُرف هو لبُّ حياة النّاس العمليّة، الحاكم والمنظّم لكثير من المعاملات بينهم، وبما أنّ أعراف النّاس متغيّرة تبعًا لتغيّر الزمان والمكان، مما يؤثر على التطبيقات الفقهية والقانونية والقضائية المختلفة. فقد آثرنا البحث في أثر العُرف في معالجة أحكام الصداق من وجهة نظر الفقه المالكي والتشريع الجزائري. من خلال طرح الإشكالية الآتية: هل للعرف أثر في معالجة أحكام الصّداق من منظور الفقه المالكي والتشريع الجزائري؟ وخلصنا في نهايته إلى أنّ كلّا من الفقه المالكي والتشريع الجزائري راعيا العُرف في أحكام الصّداق سواء في مرحلة الزواج وانحلاله، شريطة عدم مخالفة الضوابط الشرعيّة والقانونيّة لهذا المصدر التشريعي. Abstract : Both Sharia and the Algerian legislator paid great attention to the marriage contract and organized it tightly, given its danger, and surrounded it with many controls and conditions, some of which came in accordance with the customs of people considered Sharia, to facilitate them and raise their embarrassment. Accordingly, since custom is the core of people’s practical life, the ruler and regulator of many transactions between them, and since people’s customs change according to the change of time and place, which affects the various jurisprudential, legal and judicial applications. . We preferred to search on the impact of custom in treating the provisions of the dowry from the point of view of The Maliki jurisprudence and Algerian legislation, By posing the following problem: Does custom have an impact on treating the provisions of the dowry from the perspective of Maliki jurisprudence and Algerian legislation? In the end, we concluded that both The Maliki jurisprudence and Algerian legislation took into account custom in the provisions of the dowry, whether at the stage of courtship or at the stage of marriage and its permissibility, provided that the legal and legal controls of this legislative source are not violated
The Impact of Custom on the Provisions of Dower between The Maliki Jurisprudence and Algerian Legislation - Comparative Study -
مقال
Keywords: أثر العرف؛ أحكام الصداق؛ الفقه المالكي؛ التّشريع الجزائري; custom effect; dowry provisions; Maliki Fiqh; Algerian legislation